Dattasāhitya : Śrī Bēndre avara krtivicāragaḷa paricaya - Liṅgaṇṇa, Simpi, 1905- (SAMP early 20th-century Indian books project ;)
On the works of Dattatreya Ramachandra Bendre, b. 1896, Kannada author.